Exploring gender perceptions of risk of HIV infection and related behaviour among elderly men and women of Ga-Rankuwa, Gauteng Province, South Africa - Eucebious Lekalakala-Mokgele (Taylor & Francis Group, 2016)
The literature shows that there are important differences between women and men in the underlying mechanisms of transmission of HIV infection and AIDS, as well as in the social and economic consequences of HIV/AIDS. These stem from sexual behaviour and socially constructed 'gender' differences between women and men in roles and responsibilities. Despite the fact that numerous gender-related sociocultural factors influence HIV/AIDS protective behaviours, little gender specificity is included in HIV prevention among the elderly. In order to close this gap, this study explored gender-related perceptions of risk of HIV infection among elderly men and women of Ga-Rankuwa in Gauteng Province, South Africa. This qualitative study used purposive sampling to conduct three focus group interviews with 22 women and 10 men who were above 60 years of age. Findings revealed that both genders blame each other for the spreading of HIV/AIDS. Male participants displayed the tendency to have multiple partners, whereas females accepted that males are promiscuous. Mixed perceptions about disclosure of HIV status were found. Condom use was a challenge, as men did not know how to introduce it with their wives, and some female participants indicated that men are resistant to using condoms. The elderly men also believed that women will have sex in exchange for money. It is concluded that there is a need for substantial behaviour change among both elderly males and females, which should address gender power relations. More in-depth and extensive research in this area is recommended.